Novel material for improving perovskite film, perovskite solar cell and preparation method
By using new materials composed of carbazole structure and alkoxy groups in perovskite solar cells, the roughness of the perovskite absorbing layer and the grain growth is improved, and the electron and hole recombination rate in perovskite solar cells is solved. The high problem improves the stability of electronic transmission and photoelectric conversion efficiency.
Patent Information
- Application Number
- CN202411307264.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-09-18
AI Technical Summary
Due to the rough surface and multi-grain boundary of the perovskite light absorbing layer, existing perovskite solar cells have a high chance of recombination of electrons and holes at the grain boundary, which affects the electron transport stability and photoelectric conversion efficiency.
A new material is introduced into perovskite solar cells, which consists of carbazole structure and alkoxy groups. By forming hydrogen bonds with the perovskite absorbing layer, it reduces the roughness of the absorbing layer and promotes perovskite grain growth , forming larger-sized grains, isolating the electron transport layer and hole transport layer to avoid recombination.
It effectively improves the electron transmission stability and photoelectric conversion efficiency of perovskite solar cells, and improves the filling factor and photoelectric conversion efficiency.
Smart Images

Figure CN119143656A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a novel material for improving perovskite film, a perovskite solar cell and a preparation method. Background Art
[0002] Perovskite solar cells are a new type of photovoltaic cell. They have a wide spectral absorption range, simple preparation process and low cost, so they are widely popular. At present, although the photoelectric conversion efficiency of perovskite solar cells has been greatly improved, the perovskite light absorption layer (i.e., perovskite film) has a relatively rough surface and many grain boundaries in the perovskite light absorption layer, resulting in a high probability of electrons and holes recombinating at the grain boundaries, which affects electron transmission and the stability of the electron transport layer. Summary of the invention
[0003] In view of this, the present invention provides a new material for improving perovskite film, a perovskite solar cell and a preparation method. The new material is arranged between the electron transport layer and the perovskite light absorbing layer (i.e., the perovskite film) in the perovskite solar cell, which is beneficial to promote the formation of larger perovskite grains and effectively reduce the roughness of the surface of the perovskite light absorbing layer, thereby improving the electron transport stability, filling factor and photoelectric conversion efficiency.
[0004] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0005] In the first aspect, the present invention provides a novel material for improving perovskite film, the molecular structure of the novel material
[0006] As shown in general formula (I):
[0007] General formula (I)
[0008]
[0009] Wherein, R1 and R2 are alkyl groups, and R1 and R2 are the same or different.
[0010] Optionally, R1 and R2 are both alkyl groups having 1 to 6 carbon atoms.
[0011] Optionally, R1 is methyl or n-hexyl; R2 is methyl or n-hexyl.
[0012] In a second aspect, an embodiment of the present invention provides a perovskite solar cell, comprising: a substrate, an electron transport layer, a perovskite light absorbing layer, a hole transport layer, and a top electrode stacked in sequence;
[0013] The perovskite solar cell also includes a passivation layer arranged between the electron transport layer and the perovskite light absorbing layer, and the passivation layer is formed based on the new material for improving the perovskite film provided in the above-mentioned first aspect embodiment.
[0014] Optionally, the passivation layer is formed by coating an organic solution containing the novel material on the electron transport layer and the perovskite light absorbing layer.
[0015] Optionally, the passivation layer is obtained by the following operations:
[0016] coating an organic solution containing the novel material on the electron transport layer to form a wet organic film;
[0017] A precursor solution for preparing a perovskite light-absorbing layer is coated on a wet organic film, and then annealed to form a stacked passivation layer and the perovskite light-absorbing layer on the electron transport layer.
[0018] Optionally, the thickness of the passivation layer is 60nm~85nm.
[0019] Optionally, the concentration of the novel material in the organic solution for forming the passivation layer is 0.7 mg / mL to 1.3 mg / mL.
[0020] Optionally, the coating rate of the organic thin film is 2500 rpm / s to 3500 rpm / s.
[0021] Optionally, the coating time of the organic film is 20s~35s.
[0022] Optionally, the passivation layer is obtained by the following operations:
[0023] coating an organic solution containing the novel material on the electron transport layer to form a wet organic film;
[0024] The precursor solution for preparing the perovskite light-absorbing layer is coated on the wet organic film, and then annealed to form a stacked passivation layer and a perovskite light-absorbing layer on the electron transport layer.
[0025] In a third aspect, the present invention provides a method for preparing the novel material provided in the embodiment of the first aspect, comprising:
[0026] Step A, synthesizing 1,4-bis(3,6-dibromo-9H-carbazole-9-yl)benzene by using 1,4-di(9H-carbazole-9-yl)benzene;
[0027] Step B: 1,4-bis(3,6-bis(4-(3,6-dimethoxy-9H-carbazole-9-yl)phenyl)-9H-carbazole-9-yl)benzene is synthesized by using 1,4-bis(3,6-dibromo-9H-carbazole-9-yl)benzene and 3,6-dialkoxy-9-(4-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)-phenyl)-9H-carbazole.
[0028] Optionally, step A includes:
[0029] Step A1, mixing 1,4-di(9H-carbazole-9-yl)benzene and N-bromosuccinimide to form a mixture;
[0030] Step A2, tetrahydrofuran (THF) is added to the mixture, and the reaction temperature is controlled at 95-105° C. and the reaction time is 7-9 h to synthesize 1,4-bis(3,6-dibromo-9H-carbazole-9-yl)benzene.
[0031] Optionally, step B comprises: mixing 1,4-bis(3,6-dibromo-9H-carbazole-9-yl)benzene and 3,6-dialkoxy-9-(4-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)-phenyl)-9H-carbazole, adding a certain amount of carbonate, a compound containing bistriphenylphosphine and an organic solvent, and controlling the reaction temperature to 115-125° C. and the reaction time to 7-9 hours to synthesize 1,4-bis(3,6-bis(4-(3,6-dimethoxy-9H-carbazole-9-yl)phenyl)-9H-carbazole-9-yl)benzene.
[0032] Optionally, the carbonate is potassium carbonate and / or sodium carbonate.
[0033] Optionally, the mass ratio of 1,4-di(9H-carbazole-9-yl)benzene to N-bromosuccinimide is 1:2 to 1:4.5.
[0034] Optionally, the mass volume ratio (g:mL) of the mixture formed in step A1 to tetrahydrofuran is 1:10-1:20.
[0035] Optionally, the mass ratio of 3,6-dialkoxy-9-(4-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)-phenyl)-9H-carbazole to 1,4-bis(3,6-dibromo-9H-carbazole-9-yl)benzene is 1:1.2 to 1:1.5.
[0036] Optionally, the mass ratio of the compound containing bistriphenylphosphine, the carbonate and the 3,6-dialkoxy-9-(4-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)-phenyl)-9H-carbazole is 1:(4.2~4.6):(5.8~6.2).
[0037] Optionally, the mass volume ratio of 3,6-dialkoxy-9-(4-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)-phenyl)-9H-carbazole to the organic solvent is (g:mL) 1:34-1:57.
[0038] The technical solution of the first aspect of the above invention has the following advantages or beneficial effects:
[0039] The novel material for improving the perovskite film provided by the embodiment of the present invention is applied between the electron transport layer and the perovskite light absorption layer in the perovskite solar cell. Due to the presence of multiple carbazole structures in the molecular structure of the novel material, hole transport is facilitated, and nitrogen atoms are introduced for the growth of perovskite grains in the perovskite light absorption layer, so that the perovskite grains are larger. That is, the presence of the novel material is conducive to promoting the formation of larger perovskite grains in the perovskite light absorption layer, which is conducive to electron transport. It also forms hydrogen bonds with the perovskite in the perovskite light absorption layer through multiple alkoxy groups, which helps to make the surface of the perovskite light absorption layer smoother and reduce the roughness of the perovskite light absorption layer. It can also better isolate the electron transport layer and the hole transport layer, avoid the electron transport layer and the hole transport layer from compounding at the grain boundary of the perovskite light absorption layer, so as to effectively improve the stability of electron transport in the perovskite solar cell.
[0040] In addition, this new material is applied between the electron transport layer and the perovskite light-absorbing layer in perovskite solar cells. By reducing the roughness of the perovskite light-absorbing layer, it can effectively improve the filling factor of the perovskite solar cell, thereby improving the photoelectric conversion efficiency of the perovskite solar cell. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 is a schematic diagram of a partial cross-sectional structure of a perovskite solar cell according to an embodiment of the present invention;
[0042] Figure 2 is a schematic diagram of the main process of a method for preparing a novel material according to an embodiment of the present invention;
[0043] Figure 3 is a schematic diagram of a chemical reaction formula for preparing an intermediate product in a preparation process of a novel material according to an embodiment of the present invention;
[0044] Figure 4 is a schematic diagram of a chemical reaction formula for preparing a new material in a preparation process of a new material according to an embodiment of the present invention;
[0045] Figure 5 is a schematic diagram of the main process of a method for preparing a perovskite solar cell according to an embodiment of the present invention;
[0046] Figure 6 is a performance comparison diagram of a perovskite solar cell prepared based on Example 2 and a comparative example according to an embodiment of the present invention;
[0047] Figure 7 is an atomic force microscope comparison diagram of the light absorbing layer perovskite light absorbing layer prepared based on Example 2 and the comparative example according to an embodiment of the present invention;
[0048] Figure 8 It is a scanning electron microscope comparison picture of the perovskite light absorbing layer prepared based on Example 2 and the comparative example according to the embodiment of the present invention.
[0049] The reference numerals are as follows:
[0050] 10-substrate; 20-electron transport layer; 30-passivation layer; 40-perovskite light absorption layer; 50-hole transport layer; 60-top electrode. DETAILED DESCRIPTION
[0051] The novel material for improving the perovskite film provided in the embodiment of the present invention is mainly used in perovskite solar cells and perovskite solar cell preparation processes. In addition, according to the needs and the functions and effects of the novel material for improving the perovskite film provided in the embodiment of the present invention, the novel material can also be applied to other optoelectronic devices containing perovskite films, such as light-emitting devices, transistors, sensors, etc.
[0052] It is worth noting that the perovskite solar cell targeted by the embodiment of the present invention can be a single-junction perovskite solar cell or a stacked perovskite solar cell. Among them, the single-junction perovskite solar cell comprises a solar cell structure of a multi-layer thin film structure such as an electron transport layer, a perovskite light absorbing layer (that is, the above-mentioned perovskite film), a hole transport layer and an electrode layer, which absorbs light through the perovskite light absorbing layer and generates electron-hole pairs, contacts with the electron transport layer to form an electron transport channel, and contacts with the hole transport layer to form a hole transport channel. That is, the single-junction perovskite solar cell realizes photoelectric conversion through the "sandwich" structure of electron transport layer-perovskite light absorbing layer-hole transport layer. The stacked perovskite solar cell can be understood as stacking the "electron transport layer-perovskite light absorbing layer-hole transport layer" structure on the basis of crystalline silicon or amorphous silicon solar cells (such as perovskite solar cells, crystalline silicon solar cells, thin-film solar cells, etc.), and the "electron transport layer-perovskite light absorbing layer-hole transport layer" structure and the stacked solar cell are connected in series to form a "series" battery that can absorb a wider solar spectrum. Therefore, for tandem perovskite solar cells, there can be full perovskite tandem cells, crystalline silicon / perovskite tandem cells, thin film cells (such as copper indium gallium selenide) / perovskite tandem cells, etc.
[0053] Whether it is a single-junction perovskite solar cell or a stacked perovskite solar cell, since the perovskite light-absorbing layer has a relatively rough surface and many grain boundaries, the probability of electrons and holes recombining at the grain boundaries is relatively large, which affects the electron transport and the stability of the electron transport layer, and affects the photoelectric conversion performance and fill factor of the perovskite solar cell.
[0054] In order to solve the problems existing in the existing perovskite solar cells, the embodiments of the present invention provide a new material for improving the perovskite film, a perovskite solar cell and a preparation method, which aims to promote the formation of larger perovskite grains and reduce the roughness of the perovskite light-absorbing layer by adding a layer of organic material containing the new material, thereby avoiding the recombination of electrons and holes at the grain boundaries, so as to effectively improve the stability of electron transmission in the perovskite solar cell, and effectively improve the photoelectric conversion efficiency of the perovskite solar cell and the fill factor of the perovskite solar cell.
[0055] The novel material for improving the perovskite film provided in the embodiment of the present invention has a molecular structure as shown in general formula (I):
[0056] General formula (I):
[0057]
[0058] Wherein, R1 and R2 are alkyl groups, and R1 and R2 are the same or different.
[0059] Wherein, the alkyl groups of R1 and R2 may be straight-chain structures or branched structures. Preferably, the alkyl groups of R1 and R2 have 1 to 6 carbon atoms. More preferably, the alkyl groups of R1 and R2 are straight-chain structures and R1 and R2 are the same. Further preferably, R1 is methyl or n-hexyl; R2 is methyl or n-hexyl.
[0060] Among them, the novel material for improving the perovskite film is generally applied between the electron transport layer 20 and the perovskite light absorption layer 40 in the perovskite solar cell. The structure of the general formula (I) is convenient for preparing the novel material, and at the same time, it can ensure that the novel material has more carbazole structures, so as to provide more hydrogen bonds for the perovskite light absorption layer 40 and form a better fit with the perovskite light absorption layer 40.
[0061] Furthermore, by designing the molecular structure of the above-mentioned new material to be a symmetrical structure, it is possible to provide the perovskite light absorption layer 40 with as many hydrogen bonds as possible, thereby ensuring that it is used between the electron transport layer 20 and the perovskite light absorption layer 40 in the perovskite solar cell. This can reduce the roughness of the perovskite light absorption layer 40 and is beneficial to the growth of perovskite grains in the perovskite light absorption layer 40.
[0062] The materials required to form the new material include: 1,4-di(9H-carbazole-9-yl)benzene, N-bromosuccinimide, tetrahydrofuran, 3,6-dialkoxy-9-(4-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)-phenyl)-9H-carbazole, potassium carbonate / sodium carbonate and a compound containing bistriphenylphosphine. The two alkyl groups in the 3,6-dialkoxy group in 3,6-dialkoxy-9-(4-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)-phenyl)-9H-carbazole correspond to the above R1 and R2, respectively. The above potassium carbonate / sodium carbonate means that the materials required for the new material can be potassium carbonate, sodium carbonate, or a mixture of potassium carbonate and sodium carbonate.
[0063] The above-mentioned new material provided by the embodiment of the present invention is applied between the electron transport layer 20 and the perovskite light absorption layer 40 in the perovskite solar cell. The presence of multiple carbazole structures in the molecular structure of the new material is conducive to hole transport, and nitrogen atoms are introduced into the growth of perovskite grains in the perovskite light absorption layer 40, so that the perovskite grains are larger (that is, the presence of the new material is conducive to promoting the formation of larger perovskite grains in the perovskite light absorption layer 40), which is conducive to electron transport, and multiple alkoxy groups are used to form hydrogen bonds with the perovskite in the perovskite light absorption layer 40, which helps to make the surface of the perovskite light absorption layer 40 smoother, reduce the roughness of the perovskite light absorption layer 40, and can better isolate the electron transport layer 20 and the hole transport layer 50, avoid the electron transport layer 20 and the hole transport layer 50 from compounding at the grain boundary of the perovskite light absorption layer 40, so as to effectively improve the stability of electron transport in the perovskite solar cell.
[0064] In addition, the new material is applied between the electron transport layer 20 and the perovskite light absorbing layer 40 in the perovskite solar cell. By reducing the roughness of the perovskite light absorbing layer 40, the filling factor and photoelectric conversion efficiency of the perovskite solar cell can be effectively improved.
[0065] Furthermore, an embodiment of the present invention provides a perovskite solar cell. Figure 1 FIG. 4 is a schematic diagram showing a partial cross-sectional structure of the perovskite solar cell. Figure 1As shown, the perovskite solar cell provided by the embodiment of the present invention may include: a substrate 10, an electron transport layer 20, a perovskite light absorbing layer 40, a hole transport layer 50 and a top electrode 60 stacked in sequence. In addition, the perovskite solar cell may also include a passivation layer 30 disposed between the electron transport layer 20 and the perovskite light absorbing layer 40, and the passivation layer 30 is formed based on the novel material shown in the above general formula (I) for improving the perovskite film provided by the above embodiment. Among them, the passivation layer 30 and the perovskite light absorbing layer 40 are bonded. The passivation layer 30 and the perovskite light absorbing layer 40 are bonded generally means that the passivation layer 30 and the perovskite light absorbing layer 40 are in direct contact, and there is no other functional layer between them.
[0066] Among them, other functional layers such as an anti-reflection layer and a conductive layer may also be arranged on the hole transport layer 50 .
[0067] In addition, the thickness of the passivation layer 30 may be 60 nm to 85 nm. For example, the thickness of the passivation layer 30 may be 60 nm, 62 nm, 65 nm, 67 nm, 69 nm, 70 nm, 72 nm, 75 nm, 78 nm, 80 nm, 82 nm, 85 nm, etc.
[0068] The presence of multiple carbazole structures in the passivation layer 30 formed by the new material is beneficial to the transmission of holes in the hole transport layer 50 located on the perovskite light absorption layer 40, and nitrogen atoms are introduced into the growth of perovskite grains in the perovskite light absorption layer 40 to make the perovskite grains larger, which is beneficial to the electron transport in the electron transport layer 20 located under the perovskite light absorption layer 40. Hydrogen bonds are formed by the action of multiple alkoxy groups with the perovskite in the perovskite light absorption layer 40, which helps to make the surface of the perovskite light absorption layer 40 smoother and reduce the roughness of the perovskite light absorption layer 40. The electron transport layer 20 and the hole transport layer 50 can be better isolated to avoid the electron transport layer 20 and the hole transport layer 50 from being compounded at the grain boundary of the perovskite light absorption layer 40, so as to effectively improve the stability of electron transport in the perovskite solar cell.
[0069] In addition, the passivation layer 30 formed by the novel material can effectively reduce the roughness of the perovskite light absorbing layer 40 and can effectively improve the filling factor and photoelectric conversion efficiency of the perovskite solar cell.
[0070] The passivation layer 30 of the perovskite solar cell may be formed by coating an organic solution containing the novel material on the electron transport layer 20 .
[0071] Specifically, the passivation layer 30 is formed on the electron transport layer 20 by the following operations:
[0072] Applying an organic solution containing the novel material on the electron transport layer 20 to form a wet organic film;
[0073] A precursor solution for preparing the perovskite light absorbing layer 40 is coated on the wet organic film, and then annealed to form a stacked passivation layer 30 and the perovskite light absorbing layer 40 on the electron transport layer 20 .
[0074] The passivation layer 30 can be formed into a wet organic film by spin coating, spray coating or scraping coating.
[0075] The concentration of the novel material in the organic solution used to form the wet organic film is 0.7-1.3 mg / mL. For example, the concentration of the novel material in the organic solution can be 0.7 mg / mL, 0.8 mg / mL, 0.9 mg / mL, 1.0 mg / mL, 1.1 mg / mL, 1.2 mg / mL, 1.3 mg / mL, etc.
[0076] Furthermore, the coating rate of the wet organic film is generally 2500rpm / s~3500rpm / s. For example, the coating rate of the wet organic film may be 2500rpm / s, 2600rpm / s, 2750rpm / s, 2900rpm / s, 3000rpm / s, 3100rpm / s, 3300rpm / s, 3500rpm / s, etc.
[0077] Furthermore, the coating time of the wet organic film may be 20s to 35s. For example, the coating time of the wet organic film may be 20s, 21s, 22s, 24s, 25s, 27s, 29s, 30s, 32s, 34s, 35s, etc.
[0078] By first forming a wet organic film with a new material and performing annealing treatment after preparing the perovskite light absorbing layer 40, the flatness of the perovskite light absorbing layer 40 is ensured. In addition, during the treatment process, the carbazole structure in the passivation layer 30 introduces nitrogen atoms into the perovskite light absorbing layer 40 to make the perovskite grains larger. In addition, during the treatment process, multiple alkoxy groups introduced through the passivation layer 30 react with the perovskite in the perovskite light absorbing layer 40 to form hydrogen bonds, which helps to make the surface of the perovskite light absorbing layer smoother, reduce the roughness of the perovskite light absorbing layer 40, and avoid the electron transport layer 20 and the hole transport layer 50 from being recombined at the grain boundary of the perovskite light absorbing layer 40, so as to effectively improve the stability of electron transmission of the perovskite solar cell, and can effectively improve the filling factor of the perovskite solar cell, thereby improving the photoelectric conversion efficiency of the perovskite solar cell.
[0079] Furthermore, an embodiment of the present invention provides a method for preparing a new type of material. Figure 2 The main flow diagram of the method for preparing the novel material provided by the embodiment of the present invention is shown. Figure 2 As shown, the preparation method of the novel material may include:
[0080] Step S201: synthesizing 1,4-bis(3,6-dibromo-9H-carbazole-9-yl)benzene by using 1,4-di(9H-carbazole-9-yl)benzene;
[0081] The chemical reaction formula for synthesizing 1,4-bis(3,6-dibromo-9H-carbazole-9-yl)benzene in this step is as follows: Figure 3 shown.
[0082] Specifically, the process of synthesizing 1,4-bis(3,6-dibromo-9H-carbazole-9-yl)benzene in this step can be: mixing 1,4-di(9H-carbazole-9-yl)benzene with N-bromosuccinimide (NBS) to form a mixture; adding tetrahydrofuran (THF) to the mixture, and controlling the reaction temperature to 95-105° C. and the reaction time to 7-9 hours to synthesize 1,4-bis(3,6-dibromo-9H-carbazole-9-yl)benzene.
[0083] In order to control the amount of each raw material used and effectively improve the yield of 1,4-bis(3,6-dibromo-9H-carbazole-9-yl)benzene, the mass ratio of 1,4-bis(9H-carbazole-9-yl)benzene and N-bromosuccinimide (C4H4BrNO2, NBS) is 1:2~1:4.5. That is, 1g of 1,4-bis(9H-carbazole-9-yl)benzene is mixed with 2~4.5g of N-bromosuccinimide. For example, the mass ratio of 1,4-bis(9H-carbazole-9-yl)benzene to N-bromosuccinimide can be 1:2, 1:2.2, 1:2.5, 1:2.8, 1:3, 1:3.3, 1:3.5, 1:3.7, 1:4, 1:4.2, 1:4.5, etc. By controlling the mass ratio of 1,4-di(9H-carbazole-9-yl)benzene to N-bromosuccinimide, the waste of the raw materials of 1,4-di(9H-carbazole-9-yl)benzene and N-bromosuccinimide can be reduced as much as possible, thereby ensuring the yield of the intermediate product in the subsequent step S202.
[0084] In addition, in this step, the mass volume ratio of the mixture formed by mixing 1,4-di(9H-carbazole-9-yl)benzene and N-bromosuccinimide to tetrahydrofuran is 1:10-1:20, wherein the mass volume ratio means that the volume (mL) of tetrahydrofuran added per 1g of the mixture is 10-20mL. The volume of tetrahydrofuran added to 3g of the mixture is 30-60mL. For example, the mass volume ratio of the mixture to tetrahydrofuran is 1:10, 1:12, 1:14, 1:15, 1:16, 1:17, 1:18, 1:19 and 1:20, etc.
[0085] The reaction temperature used in the reaction process of this step is 95-105°C, and the reaction time is 7-9h. For example, the reaction temperature of this step can be 95°C, 96°C, 98°C, 99°C and 100°C, and the reaction time can be 7h, 7.2h, 7.5h, 7.8h, 8h, 8.3h, 8.5h, 8.8h, 9h, etc.
[0086] Step S202: 1,4-bis(3,6-bis(4-(3,6-dimethoxy-9H-carbazole-9-yl)phenyl)-9H-carbazole-9-yl)benzene is synthesized by using 1,4-bis(3,6-dibromo-9H-carbazole-9-yl)benzene and 3,6-dialkoxy-9-(4-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)-phenyl)-9H-carbazole.
[0087] Among them, the two alkyl groups in the 3,6-dialkoxy group in 1,4-bis(3,6-dibromo-9H-carbazole-9-yl)benzene and 3,6-dialkoxy-9-(4-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)-phenyl)-9H-carbazole correspond to R1 and R2 of the formed novel material. The two alkoxy groups can be two methaneoxy groups or two n-hexaneoxy groups or a combination of one methaneoxy group and one n-hexaneoxy group. The chemical reaction formula of the novel material obtained in step S202 is as follows: Figure 4 It is worth noting that Figure 4 The reaction formula shown is a reaction formula using 3,6-dimethoxy-9-(4-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)-phenyl)-9H-carbazole as an example of a reactant. For the case where the 3,6-dialkoxy group in the reactant 3,6-dialkoxy-9-(4-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)-phenyl)-9H-carbazole is a combination of two n-hexyloxy groups or one methaneoxy group and one n-hexyloxy group, it is only necessary to replace the 3,6-dimethoxy group in the reaction formula with the corresponding alkyl group. Figure 4 The reaction formula shown is similar and will not be repeated here.
[0088] Specifically, the process of synthesizing 1,4-bis(3,6-bis(4-(3,6-dialkoxy-9H-carbazole-9-yl)phenyl)-9H-carbazole-9-yl)benzene in this step can be: 1,4-bis(3,6-dibromo-9H-carbazole-9-yl)benzene and 3,6-dialkoxy-9-(4-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)-phenyl)-9H-carbazole are mixed, and a certain amount of potassium carbonate / sodium carbonate, a compound containing bistriphenylphosphine and an organic solvent are added, and the reaction temperature is controlled to 115~125°C and the reaction time is 7~9h, so that 1,4-bis(3,6-bis(4-(3,6-dialkoxy-9H-carbazole-9-yl)phenyl)-9H-carbazole-9-yl)benzene is synthesized. For example, the reaction temperature of this step can be 115°C, 116°C, 119°C, 120°C, 122°C, 123°C, 124°C, 125°C, etc., and the reaction time can be 7h, 7.1h, 7.4h, 7.5h, 7.6h, 7.9h, 8h, 8.2h, 8.3h, 8.5h, 8.8h, 9h, etc.
[0089] Among them, the mass ratio of 3,6-dialkoxy-9-(4-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)-phenyl)-9H-carbazole to 1,4-bis(3,6-dibromo-9H-carbazole-9-yl)benzene can be 1:1.2~1:1.5. For example, the mass ratio of 3,6-dialkoxy-9-(4-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)-phenyl)-9H-carbazole to 1,4-bis(3,6-dibromo-9H-carbazole-9-yl)benzene can be 1:1.2, 1:1.3, 1:1.4, 1:1.5, etc.
[0090] Furthermore, the mass ratio of the compound containing bistriphenylphosphine, potassium carbonate / sodium carbonate and 3,6-dialkoxy-9-(4-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)-phenyl)-9H-carbazole is 1:(4.2~4.6):(5.8~6.2), that is, the compound containing bistriphenylphosphine: potassium carbonate / sodium carbonate: 3,6-dialkoxy-9-(4-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)-phenyl)-9H-carbazole = 1:(4.2~4.6):(5.8~6.2). For example, the mass ratio of the compound containing bistriphenylphosphine: potassium carbonate / sodium carbonate: 3,6-dialkoxy-9-(4-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)-phenyl)-9H-carbazole can be 1:4.2:5.8, 1:4.4:6, 1:4.5:6.2, 1:4.6:6.1, 1:4.6:6.2, etc. Among them, the compound containing bistriphenylphosphine generally uses tetrakistriphenylphosphine palladium, and the mass ratio of potassium carbonate / sodium carbonate, tetrakistriphenylphosphine palladium and monocarbazole structure is controlled to ensure the target product is obtained and effectively improve the yield of the target product.
[0091] Further, in this step, the mass volume ratio of 3,6-dialkoxy-9-(4-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)-phenyl)-9H-carbazole to the organic solvent is 1:34-1:57, that is, the volume of the organic solvent added per 1g of 3,6-dialkoxy-9-(4-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)-phenyl)-9H-carbazole is 34-57mL. For example, the volume mass ratio of the organic solvent to the single carbazole structure can be 1:34, 1:35, 1:38, 1:40, 1:42, 1:45, 1:47, 1:48, 1:50, 1:52, 1:55, 1:57, etc. For example, for 0.88 g of 3,6-dialkoxy-9-(4-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)-phenyl)-9H-carbazole, the volume of the added organic solvent can be 30 mL, 35 mL, 40 mL, 45 mL, 50 mL, etc. The organic solvent is generally a benzene solvent, preferably, toluene.
[0092] In the embodiment of the present invention, the mass ratio of 1,4-di(9H-carbazole-9-yl)benzene to N-bromosuccinimide is controlled by combination: 1:2 to 1:4.5, the mass volume ratio of the mixture formed by 1,4-di(9H-carbazole-9-yl)benzene and N-bromosuccinimide to tetrahydrofuran is 1:10 to 1:20, the mass ratio of 3,6-dialkoxy-9-(4-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)-phenyl)-9H-carbazole to the intermediate product is 1:1.2 to 1:1.5, a compound containing bistriphenylphosphine, potassium carbonate / sodium carbonate and 3,6-dialkoxy-9-(4-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl) The mass ratio of 3,6-dialkoxy-9-(4-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)-phenyl)-9H-carbazole to the organic solvent is 1:34 ~1:57, which can effectively control the target product to be Figure 4 The product shown can effectively improve the yield of the target product.
[0093] Furthermore, an embodiment of the present invention provides a method for preparing a perovskite solar cell. Figure 5 The main process diagram of the method for preparing a perovskite solar cell provided by an embodiment of the present invention is shown. Figure 5 As shown, the method for preparing the perovskite solar cell may include:
[0094] Step S501: using an organic solution containing the novel material provided in the above embodiment to form a wet organic film on the formed electron transport layer 20;
[0095] The concentration of the novel material in the organic solution used in step S501 is 0.7-1.3 mg / mL. For example, the concentration of the novel material in the organic solution can be 0.7 mg / mL, 0.8 mg / mL, 0.9 mg / mL, 1.0 mg / mL, 1.1 mg / mL, 1.2 mg / mL, 1.3 mg / mL, etc.
[0096] Step S502: preparing a perovskite light absorbing layer 40 on the wet organic film and performing annealing treatment;
[0097] Step S503: preparing a hole transport layer 50 on the perovskite light absorption layer 40 and performing annealing treatment.
[0098] The preparation method of the perovskite solar cell first forms a wet organic film with a new material, and performs annealing treatment after preparing the perovskite light absorbing layer 40, so as to ensure the flatness of the perovskite light absorbing layer 40. In addition, in the treatment process, the carbazole structure introduced by the passivation layer 30 introduces nitrogen atoms into the perovskite light absorbing layer 40, so that the perovskite grains are larger, and multiple alkoxy groups are introduced to react with the perovskite in the perovskite light absorbing layer 40 to form hydrogen bonds, which helps to make the surface of the perovskite light absorbing layer 40 smoother, reduce the roughness of the perovskite light absorbing layer 40, and avoid the electron transport layer 20 and the hole transport layer 50 from being recombined at the grain boundary of the perovskite light absorbing layer 40, so as to effectively improve the stability of electron transmission of the perovskite solar cell, and can effectively improve the filling factor of the perovskite solar cell, thereby improving the photoelectric conversion efficiency of the perovskite solar cell.
[0099] The technical solution provided by the present invention is further explained below based on specific embodiments. The following explanation is only used to explain the relevant inventions of this application and is not a limitation of the present invention. The embodiments and drawings only show the parts related to the invention.
[0100] Example 1: New material preparation process
[0101] Step S1, according to the mass ratio of 1: 2.1, weighed 1,4-di(9H-carbazole-9-yl)benzene and N-bromosuccinimide are mixed, a certain amount of solvent tetrahydrofuran is added (wherein, the mass volume ratio of 1,4-di(9H-carbazole-9-yl)benzene to tetrahydrofuran is 1:30, that is, 30 ml of tetrahydrofuran is added for every 1 g of 1,4-di(9H-carbazole-9-yl)benzene), and reacted at 100° C. for 8 h to obtain the product 1,4-bis(3,6-dibromo-9H-carbazole-9-yl)benzene. The reaction formula of this step is as follows: Figure 3 shown.
[0102] Step S2, mixing the product obtained in step S1 with a certain amount of 3,6-dimethoxy-9-(4-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)phenyl)-9H-carbazole (wherein the mass ratio of 3,6-dimethoxy-9-(4-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)phenyl)-9H-carbazole to the product obtained in step A1 is 1:1.2), and adding a certain amount of potassium carbonate and tetrakistriphenylphosphine palladium (the tetrakistriphenylphosphine palladium, potassium carbonate and 3,6-dimethoxy-9-(4-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)phenyl)-9H-carbazole. The mass ratio of carbazole is 1:4.4:6), toluene (the volume mass ratio of toluene to 3,6-dimethoxy-9-(4-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)phenyl)-9H-carbazole is 45:1, that is, 45 ml of toluene is added to every 1 g of 3,6-dimethoxy-9-(4-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)phenyl)-9H-carbazole), and the mixture is reacted at 120°C for 8 hours to obtain the target product 1,4-bis(3,6-bis(4-(3,6-dimethoxy-9H-carbazole-9-yl)phenyl)-9H-carbazole-9-yl)benzene, that is, a new material. The reaction formula of this step is as follows Figure 4 shown.
[0103] Embodiment 2:
[0104] Step S3: cleaning the conductive glass as the substrate 10 with a mixture of glass cleaning liquid and deionized water (the volume ratio of the glass cleaning liquid to deionized water in the mixture is 1:50), deionized water, and acetone in sequence, and then drying with dry nitrogen;
[0105] Step S4: treating the conductive glass in step S3 under ultraviolet ozone conditions for 20 minutes;
[0106] Step S5: Spin-coating a SnO2 layer on the conductive glass obtained in step S4;
[0107] The specific process of step S5 is as follows: first, the SnO2 nano-dispersion liquid is mixed with deionized water in a volume ratio of 1:4, and ultrasonicated for 15 minutes, and then spin-coated on the conductive glass. During the spin-coating process, the spin-coating speed is controlled to be 3000 rpm, the spin-coating time is 30 s, and the spin-coating acceleration is 3000 rpm / s. After the spin-coating is completed, the conductive glass is transferred to a heating table and annealed at 150°C for 30 minutes, thereby obtaining a dense SnO2 electron transport layer 20;
[0108] Step S6: treating the electron transport layer 20 obtained in step S5 under ultraviolet ozone conditions for 20 min;
[0109] Step S7: weigh a certain amount of 1,4-bis(3,6-bis(4-(3,6-dimethoxy-9H-carbazole-9-yl)phenyl)-9H-carbazole-9-yl)benzene prepared in Example 1, and dissolve it in a certain amount of chlorobenzene to prepare a solution with a concentration of 1 mg / mL;
[0110] Step S8: Spin coating the solution obtained in S7 onto the electron transport layer 20 to form a wet organic thin film, wherein the spin coating speed is 3000 rpm, the time is 30 s, and the acceleration is 3000 rpm / s;
[0111] Step S9: quickly spin-coating the precursor solution on the organic wet film, and performing annealing treatment to obtain a stacked passivation layer 30 and a perovskite light absorbing layer 40 on the electron transport layer 20;
[0112] Specifically, the process of step S9 is as follows: 33.7 mg MACl, 705 mg PbI2 and 240 mg FAI are dissolved in 1 mL DMF / DMSO (volume ratio of 8:1), and then stirred at room temperature (25°C) for 8 h to obtain a precursor solution; after stirring, the precursor solution is spin-coated onto the conductive glass treated in step S8, and the spin coating is divided into two steps, the first step is a rotation speed of 1000 rpm, a time of 10 s, and an acceleration of 1000 rpm / s; in the second step, the rotation speed is 5000 rpm, the time is 30 s, and the acceleration is 5000 rpm / s, and 120 μL of anti-solvent ethyl acetate is slowly added in the last 10 seconds. After the spin coating is completed, the conductive glass spin-coated with the precursor solution is placed on a hot plate at 100°C for annealing for 1 h to obtain a perovskite light absorbing layer 40;
[0113] Step S10: After the perovskite light absorbing layer 40 obtained in S9 is cooled, a hole transport layer 50 is prepared;
[0114] The specific process is as follows: 520 mg of Li-TFSI is dissolved in 1 mL of acetonitrile solution to obtain a Li-TFSI solution; 300 mg of Co-TFSI is dissolved in 1 mL of acetonitrile solution to obtain a Co-TFSI solution; 72.3 mg of Spiro-OMeTAD is dissolved in 1 mL of chlorobenzene, and stirred evenly to obtain a 72.3 mg / mL Spiro-OMeTAD solution; 18 μL of Li-TFSI solution and 29 μL of Co-TFSI solution are added to the Spiro-OMeTAD solution, and stirred at room temperature for 30 minutes to obtain a mixed solution for preparing a hole transport layer 50;
[0115] The mixed solution for preparing the hole transport layer 50 is coated on the perovskite light absorbing layer 40 by spin coating, the spin coating speed is 3000 rpm, the time is 30 s, the acceleration is 3000 rpm / s, and annealing is performed to obtain the hole transport layer 50;
[0116] Step S11: evaporating a top electrode 60 on the hole transport layer 50; thus, a perovskite solar cell is obtained.
[0117] Specifically, in this step, a metal Au electrode with a thickness of 81 nm is prepared on the hole transport layer 50 .
[0118] Comparative Example:
[0119] This comparative example is prepared only by steps S3 to S6 and steps S9 to S11 in the above embodiment 2, and in the step corresponding to the above step S9 in this comparative example, the precursor solution is directly spin-coated on the electron transport layer 20, and annealing is performed to obtain the perovskite light absorbing layer 40 directly coated on the electron transport layer 20. That is, the above steps S7 and S8 are omitted in this comparative example.
[0120] By performing performance tests on the perovskite solar cells obtained in the comparative example and Example 2 and characterizing the surface of the perovskite light absorbing layer 40, the following results are obtained: Figure 6 The performance comparison chart of perovskite solar cells shown in the figure is as follows: Figure 7 Atomic force microscope comparison chart shown and Figure 8 The scanning electron microscope comparison image of the perovskite light absorbing layer 40 is shown.
[0121] from Figure 6 It can be seen that the photovoltaic parameters of the comparative device are: the short-circuit current density JSC is 23.85 mA / cm 2 , the open circuit voltage VOC is 1.123V, the fill factor FF is 80.31%, and the photoelectric conversion efficiency PCE is 21.51%; the photovoltaic parameters of the device of Example 2 are: the short circuit current density JSC is 24.00mA / cm 2 , the open circuit voltage VOC is 1.144V, the fill factor FF is 85.04%, and the photoelectric conversion efficiency PCE is 23.35%. It can be clearly seen from the figure that the new material provided by the embodiment of the present invention forms a passivation layer 30 between the electron transport layer 20 and the perovskite light absorption layer 40, and the passivation layer 30 can achieve doping of the perovskite light absorption layer 40 and passivation of the interface of the perovskite light absorption layer 40. Compared with the perovskite solar cell of the comparative example prior art, the short circuit current density JSC and the open circuit voltage VOC are improved, and the most obvious improvement is the fill factor FF, which has increased from 80.31% to 85.04%.
[0122] The perovskite light absorbing layer 40 of the comparative example and Example 2 was characterized by atomic force microscopy, and the results were as follows: Figure 7 Atomic force microscope comparison diagram shown. In the process of observing the perovskite light absorbing layer 40 of the comparative example and Example 2 by atomic force microscope, it is found that the surface roughness of the perovskite light absorbing layer 40 can be reduced by introducing the passivation layer 30 formed by the novel material provided in the embodiment of the present invention between the electron transport layer 20 and the perovskite light absorbing layer 40 of the perovskite solar cell. Specifically, in the process of observing the perovskite light absorbing layer 40 in the comparative example by atomic force microscope, it is found that the average roughness of the perovskite light absorbing layer 40 is 27.5 nm. In the perovskite solar cell with the passivation layer 30 formed by the novel material provided in the embodiment of the invention observed by atomic force microscope, the average roughness of the perovskite light absorbing layer 40 of Example 2 is reduced to 24.2 nm.
[0123] The perovskite light absorbing layers of the comparative example and Example 2 were scanned by scanning electron microscope, and the Figure 8 By comparing the morphology of the perovskite light absorbing layer of the comparative example and the morphology of the perovskite light absorbing layer 40 of Example 2 obtained by scanning electron microscopy, it can be seen that the introduction of the passivation layer 30 formed by the novel material provided in the embodiment of the present invention between the electron transport layer 20 and the perovskite light absorbing layer 40 of the perovskite solar cell can make the perovskite light absorbing layer 40 form large-sized perovskite grains, indicating that the introduction of the passivation layer 30 formed by the novel material provided in the embodiment of the present invention between the electron transport layer 20 and the perovskite light absorbing layer 40 is conducive to promoting the formation of larger perovskite grains.
[0124] The introduction provided in the above steps is only used to help understand the method, structure and core idea of the present invention. For ordinary technicians in this technical field, without departing from the principle of the present invention, several improvements and modifications can be made to the present invention, and these improvements and modifications also belong to the scope of protection of the claims of the present invention.
Claims
1. A new material for improving perovskite film, characterized in that: The molecular structure of the novel material is shown in general formula (I): General formula (I) Wherein, R1 and R2 are alkyl groups, and R1 and R2 are the same or different.
2. The novel material for improving perovskite film according to claim 1, characterized in that: R1 and R2 are both alkyl groups having 1 to 6 carbon atoms.
3. A perovskite solar cell, comprising: A substrate (10), an electron transport layer (20), a perovskite light absorbing layer (40), a hole transport layer (50) and a top electrode (60) are sequentially stacked, characterized in that it also includes a passivation layer (30) arranged between the electron transport layer (20) and the perovskite light absorbing layer (40), and the passivation layer (30) is formed based on the new material for improving the perovskite film according to claim 1 or 2.
4. The perovskite solar cell according to claim 3, characterized in that: The passivation layer (30) is formed by coating an organic solution containing the novel material on the electron transport layer (20).
5. The perovskite solar cell according to claim 4, characterized in that: The passivation layer (30) is obtained by the following operations: Applying an organic solution containing the novel material on the electron transport layer (20) to form a wet organic film; A precursor solution for preparing a perovskite light absorbing layer is coated on a wet organic film, followed by an annealing treatment, thereby forming a stacked passivation layer (30) and a perovskite light absorbing layer (40) on the electron transport layer (20).
6. The perovskite solar cell according to claim 5, characterized in that: In the organic solution containing the novel material, the concentration of the novel material is 0.7-1.3 mg / mL.
7. The method for preparing the novel material according to claim 1 or 2, characterized in that: include: Step A, synthesizing 1,4-bis(3,6-dibromo-9H-carbazole-9-yl)benzene by using 1,4-di(9H-carbazole-9-yl)benzene; Step B: 1,4-bis(3,6-bis(4-(3,6-dimethoxy-9H-carbazole-9-yl)phenyl)-9H-carbazole-9-yl)benzene is synthesized by using 1,4-bis(3,6-dibromo-9H-carbazole-9-yl)benzene and 3,6-dialkoxy-9-(4-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)-phenyl)-9H-carbazole.
8. The preparation method according to claim 7, characterized in that: Step A includes: Step A1, mixing 1,4-di(9H-carbazole-9-yl)benzene and N-bromosuccinimide to form a mixture; Step A2, adding tetrahydrofuran to the mixture, and controlling the reaction temperature to 95-105° C. and the reaction time to 7-9 h to synthesize 1,4-bis(3,6-dibromo-9H-carbazole-9-yl)benzene; or / and, Step B includes: 1,4-bis(3,6-dibromo-9H-carbazole-9-yl)benzene and 3,6-dialkoxy-9-(4-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)-phenyl)-9H-carbazole are mixed, a certain amount of carbonate, a compound containing bistriphenylphosphine and an organic solvent are added, and the reaction temperature is controlled at 115-125°C and the reaction time is 7-9h to synthesize 1,4-bis(3,6-bis(4-(3,6-dimethoxy-9H-carbazole-9-yl)phenyl)-9H-carbazole-9-yl)benzene.
9. The method for preparing the novel material according to claim 8, characterized in that: The mass ratio of the 1,4-di(9H-carbazole-9-yl)benzene to the N-bromosuccinimide is 1:2 to 1:4.5; and / or, The mass volume ratio of the mixture formed in step A1 to the tetrahydrofuran is 1 g:10 mL to 1 g:20 mL.
10. The method for preparing the novel material according to claim 8, characterized in that: The mass ratio of the 3,6-dialkoxy-9-(4-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)-phenyl)-9H-carbazole to the 1,4-bis(3,6-dibromo-9H-carbazole-9-yl)benzene is 1:1.2 to 1:1.5; and / or, The mass ratio of the bistriphenylphosphine-containing compound, the carbonate and the 3,6-dialkoxy-9-(4-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)-phenyl)-9H-carbazole is 1:(4.2-4.6):(5.8-6.2); and / or, The mass volume ratio of the 3,6-dialkoxy-9-(4-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)-phenyl)-9H-carbazole to the organic solvent is 1 g:34 mL to 1 g:57 mL.
Citation Information
Patent Citations
Preparation method of efficient and stable perovskite solar cell
CN113471364A
Carbazolyl hydrogen bond organic framework material as well as preparation method and application thereof
CN114854035A
Novel compound for organic electroluminescent device and organic electroluminescent device comprising the same
KR1020150121626A
